KOMITMEN ORGANISASIONAL MEMEDIASI DISIPLIN KERJA DAN KOMPETENSI TERHADAP KINERJA GURU SMK NEGERI DI KABUPATEN PATI (Jurnal Mahasiswa Pasca Sarjana, 2013)
The purpose of this study was to analyze the role of organizational commitment mediates labor discipline and competence on teacher performance at SMK Negeri in Pati regency The population in this study is the civil servant at SMK Negeri in Pati regency. By using the proportional heyer method obtained 132 respondents. The results of this study is the (1) job variable discipline positive and significant impact on Organizational Commitment, Job Discipline means higher than a teacher it will increase its commitment to the school. (2) Teacher Competency positive and significant impact on Organizational Commitment, means the better the competence of a teacher, the higher their organizational commitment. (3) Work Discipline has positive and significant impact on teacher performance, the higher the work discipline of a teacher it will be the higher their performance. (4) Teacher Competency positive and significant impact on teacher performance, meaning that the higher the performance, the higher competence posed. (5) organizational commitment was not significant effect on teacher performance, meaning that the higher the organizational commitment of teachers at SMK Negeri in Pati regency, had no effect on their performance, it is seen that the level of commitment organizational significance is 0.691> 0.05. Keywords: work discipline, teacher competency, organizational commitment, performance.